2019
DOI: 10.1016/j.semnephrol.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Kidney Cross-Talk in Acute Kidney Injury

Abstract: Summary The recent surge in research on the intestinal microbiota has greatly changed our understanding of human biology. Significant technical advances in DNA sequencing analysis and its application to metagenomics and metatranscriptomics has profoundly enhanced our ability to quantify and track complex microbial communities and to begin understanding their impact on human health and disease. This has led to a better understanding of the relationships between the intestinal microbiome and renal physiology/ pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 95 publications
(102 reference statements)
3
80
0
3
Order By: Relevance
“…In our study, we were interested in interpreting the extensive intra-subject variability of post-I/R creatinine concentration. Although during renal I/R many parameters can affect the severity of AKI, there are some reasons to consider microbiome as one of the possible factors playing a role in this issue [32,33]. All our main findings are summarized in Figure 4.…”
Section: Discussionmentioning
confidence: 70%
“…In our study, we were interested in interpreting the extensive intra-subject variability of post-I/R creatinine concentration. Although during renal I/R many parameters can affect the severity of AKI, there are some reasons to consider microbiome as one of the possible factors playing a role in this issue [32,33]. All our main findings are summarized in Figure 4.…”
Section: Discussionmentioning
confidence: 70%
“…Although the incidence is difficult to estimate due to variable patient characteristics, many newly developed drugs have distinct mechanisms of nephrotoxicity, making it the second most common cause of hospital-acquired AKI (4). Recent studies have revealed a close relationship between the gut microbiome and various kidney diseases; however, the association between intestinal bacteria and nephrotoxic AKI remains unclear (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In contrary, depletion of mouse gut microbiota by an antibiotic-cocktail significantly attenuates I/R-induced AKI associated with low expression of F4/80 macrophages and pro-inflammatory chemokines [ 89 ]. Intestinal microbiota modulates immune reactions in AKI through their metabolites such as short chain fatty acids, trimethylamine-N-Oxide, and D-amino acids [ 86 , 90 ]. While it is known that there is a gut-kidney cross talk, it has only recently been demonstrated that AKI can influence intestinal microbiomes.…”
Section: The Differences In Gut Microbiota Among Rodents Large Animamentioning
confidence: 99%